2021
DOI: 10.3390/ijms22052622
|View full text |Cite
|
Sign up to set email alerts
|

TNMplot.com: A Web Tool for the Comparison of Gene Expression in Normal, Tumor and Metastatic Tissues

Abstract: Genes showing higher expression in either tumor or metastatic tissues can help in better understanding tumor formation and can serve as biomarkers of progression or as potential therapy targets. Our goal was to establish an integrated database using available transcriptome-level datasets and to create a web platform which enables the mining of this database by comparing normal, tumor and metastatic data across all genes in real time. We utilized data generated by either gene arrays from the Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
434
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 597 publications
(443 citation statements)
references
References 28 publications
8
434
0
1
Order By: Relevance
“…Finally, since our results show differences depending on the type of cell line (Luminal MCF-7 and triple-negative/basal MDA-MB-231), we analyzed the differential expression of Sdc-1 in non-tumor, primary tumors and metastases tissues from breast cancer patients. For this purpose, we use the online tool TNMplot (https://www.tnmplot.com, accessed on 21 May 2021) [35]. We observed that (1) Sdc-1 is more highly expressed in the primary and metastatic tumor tissues than in non-tumor samples and (2) Sdc-1 is expressed at higher levels in primary tissues than in metastatic sites (Supplementary Figure S3A).…”
Section: String Analysis Reveals That Sdc-1 Interacts With Various Protein Targets Associated With Ha Metabolism Stemness and Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, since our results show differences depending on the type of cell line (Luminal MCF-7 and triple-negative/basal MDA-MB-231), we analyzed the differential expression of Sdc-1 in non-tumor, primary tumors and metastases tissues from breast cancer patients. For this purpose, we use the online tool TNMplot (https://www.tnmplot.com, accessed on 21 May 2021) [35]. We observed that (1) Sdc-1 is more highly expressed in the primary and metastatic tumor tissues than in non-tumor samples and (2) Sdc-1 is expressed at higher levels in primary tissues than in metastatic sites (Supplementary Figure S3A).…”
Section: String Analysis Reveals That Sdc-1 Interacts With Various Protein Targets Associated With Ha Metabolism Stemness and Developmentmentioning
confidence: 99%
“…The TNMplot database (https://www.tnmplot.com/, accessed on 21 May 2021) [35] was set up using the RNA-seq from The Cancer Genome Atlas (TCGA) repository. The database contains 11,010 samples from TCGA: 394 metastatic, 9886 tumorous and 730 normal tissues.…”
Section: Tnm and Kaplan-meier Plotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the highly upregulated genes was loaded into TNM plotter (BRCA database) to observe the differences in their expression in normal, cancerous and metastatic tissues (Figure S4a-e). 36 We observed that all the top five upregulated genes in NHMO samples as compared to NHM samples were expressed more in cancerous and metastatic breast cancer tissues as compared to normal breast tissues (Figure S4a-e). The gene signature consisting of all the five upregulated genes was observed to be expressed more in both TNBC and broad BRCA tissue database (fed into GEPIA2 application) as compared to normal tissue database (Figure S4f).…”
Section: Obs Modulates Gene Expression In Vbctsmentioning
confidence: 93%